Aplikasi Pengelolaan Kredit Perumahan Dengan Metode Kredit Risk Menggunakan PHP dan MySQL (Studi Kasus : Perum Alam Asri) - RIO ANDRIYAT KRISDIAWAN (NUANSA INFORMATIKA, 2014)
The house is a primary requirement for the fulfillment of human well-being as food and clothing. However, it turns out the need for housing is often hampered by lack of funds owned by consumers who crave own their own home. Thus, through the development of mortgage ogled as the main alternative housing finance. Mortgages is the ability to execute a purchase or hold a loan with a promise, payment will be executed at the agreed time period. This is one of the emerging credit. In extending mortgages, banks here must be selective in assessing the feasibility of the proposed by the debtor bank's assessment was conducted in order to avoid losses due to the return of loans disbursed. Thus in doing the lending bank must make an assessment based lending procedures and internal controls in order to avoid bank bad credit. It is also to be planned strategically for mortgages in the brass, especially mortgage PERUM Alam Asri. As a business developer in the field of home ownership that must be taken into account is about sorting the data consumer in the home loan application process. Both in terms of the validity of the data and supported by field monitoring. From there, the author get the idea, how to design a management application homeownership in PERUM Alam AsriÂ  which prioritizes the analysis of credit risk management. Which in essence how to manage existing credit processes to minimize credit risks that often arise. Starting from customer identity data collection in truth, filing mortgage, Customer Survey income, up to the management of the mortgage payment installments, thus minimizing credit risks exist. In designing this application, the authors use a Web-based programming languages, PHP and MySQL.Keyword : KPR, Credit Risk, PHP dan MySQL